UiTM Sarawak caring society programme with Rumah Kebajikan Kanak-kanak Batu 12 Kuching Sarawak - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
This caring society programme had been an annual programme for the Faculty of Accountancy since year 2007. During the ceremony the campus director of UiTM Sarawak had highlighted the importance of student's involvement in community service and other student's activities as part of the university objective to produce UiTM graduate model which have value such as knowledgeable, skillful, creative, analytical, independence, dynamic and possesses leadership and entrepreneurship personality.